Pengaruh Pemberian Ekstrak Sambiloto (Andrographis Paniculata Nees) Terhadap Kadar Profil Lipid Dalam Darah Tikus Putih (Rattus Norvegicus) Galur Wistar Jantan Model Hiperkolesterolemia - Dally, Juan Simon Imanuel; Manafe, Derri Tallo; Sagita, Sidarta; Amat, Anita Lindesni Shinta (Innovative: Journal Of Social Science Research, 2025)
This study was an experimental study using a post-test only control group design. Male Wistar rats were divided into six groups: normal group, negative control (high-cholesterol diet without therapy), positive control (give atorvastatin 5-6 mg/kgBW/day), and three treatment groups receiving Andrographis paniculata extract at doses of 200, 400, and 800 mg/kgBW for 14 days. Hypercholesterolemia was induced by administering duck egg yolk (8 mg/kgBW/day) and pork fat (3 mg/kgBW/day) for 14 days. Lipid level measurements were performed using a spectrophotometer on days 15 and 37. Statistical analysis was conducted using Levene’s test, Shapiro-Wilk, Kruskal-Wallis, and LSD post hoc test with SPSS. There was a significant difference in blood lipid profile levels between the treatment groups and the negative control group (p < 0.05). The administration of Andrographis paniculata extract at a dose of 800 mg/kgBW showed the highest effectiveness in reducing total cholesterol, triglycerides, and LDL levels, while increasing HDL levels compared to lower doses and atorvastatin. Andrographis paniculata extract significantly affects blood lipid profile levels in hypercholesterolemic rats. The dose of 800 mg/kgBW was the most effective in reducing total cholesterol, triglycerides, LDL, and increasing HDL. These findings support the potential of Andrographis paniculata as an alternative therapy for managing hypercholesterolemia.